Fe-Al Diffusion Bonding: Effect of reaction time on the interlayer thickness / Asmawi Ismail...[et al.] - Ismail, Asmawi; Hussain, Patthi; Mustapha, Mazli; Nuruddin, Muhd Fadhil (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
A direct diffusion bonding of marine grade aluminium alloy AA6061 and steel A36 was carried out in an argon environment at 640°C. Specimens were heated in a furnace for a holding time of 90 to 120 min under a pre-pressed condition. An interface microstructural observation revealed an increase in the thickness of this reaction layer as bonding time increased. A 33.4 μm thickness was recorded at the interfacial zone of the joint after a 120-min holding time condition. Hardness along the bonding line was measured using a micro-Vickers hardness tester. Diffusion of aluminium and iron was observed on both parent metals at the interfacial zone using scanning electron microscope (SEM) with energy dispersive spectroscopy (EDS). This experiment had proven that different content and thickness of alloy compounds were formed at various reaction time frames on the interfacial zone.